2017
DOI: 10.37134/mjm.vol6.1.4.2017
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Tradition, Making Nation: Zubir Said’s Traditionalised Film Music for Dang Anom

Abstract: The Malay-language films produced by the Cathay-Keris Studio in 1950s to 1960s Singapore were known for their 'traditional' narratives based on Malay folklore and legends set in the pre-colonial Malay world. Made during a period of nation-making in the region, these films used musical accompaniment that had to be culturally-rooted in the music of the Malay Peninsula while expressing the region's aspirations for postcolonial independence. Interestingly, this task was undertaken prominently by the film composer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Johan's account on Zubir Said's film scoring in the 1960s (Johan, 2017) confirmed that the situation in the nascent independence period was one where musicians had to work out their musical solutions in response to ongoing social changes. Johan contrasted the "traditionalised" Malay musical solution worked out by Zubir Said with the anti-feudal narrative of film and explicated the intriguing and at times contradictory facets in music-making of that time.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Johan's account on Zubir Said's film scoring in the 1960s (Johan, 2017) confirmed that the situation in the nascent independence period was one where musicians had to work out their musical solutions in response to ongoing social changes. Johan contrasted the "traditionalised" Malay musical solution worked out by Zubir Said with the anti-feudal narrative of film and explicated the intriguing and at times contradictory facets in music-making of that time.…”
Section: Literature Reviewmentioning
confidence: 96%
“…McGuire (2018) (2018) addressed the theme song of Wong Fei-Hung's legendary Kungfu films as conveying the informal transnational national anthem of the Cantonese people. On the other side, Johan (2017) conducted an intertextual study between biographies and film scores to uncover the history of Malay nationalism. The study applied musicological analysis, particularly the breakdown of musical motifs and stylistic Ave Satani Motifs Relation to Narrative Thematic Development of the Omen: An Analysis of Oscar-Winning Horror Film Music identification in Zubir Said's compositions for Hussein Hanniff's Dang Anom film.…”
Section: B Horror Film Studiesmentioning
confidence: 99%
“…Even though there were musicological analyses of several film music, they did not textually reveal the quality of its music. Most of the studies were only part of the intertextual study of the elements within a film (Johan, 2017). Hilewicz's (2021) musicological studies did not examine music from film illustrations but a piece of music prepared for the film.…”
Section: Statement Of Problemsmentioning
confidence: 99%